2004
DOI: 10.1007/s00464-003-8918-y
|View full text |Cite
|
Sign up to set email alerts
|

Staple line coverage with absorbable mesh after thoracoscopic bullectomy for spontaneous pneumothorax

Abstract: Wide coverage of the staple line with absorbable mesh is effective in preventing postoperative air leak and in decreasing the recurrence rates of PSP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
60
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 12 publications
2
60
0
Order By: Relevance
“…According to the American College of Chest Physicians (21) and BTS guidelines (4), the preferred approach for prevention of recurrent pneumothorax is still surgical because of lower recurrence rates compared with instillation of sclerosing agents through a chest tube. However, the recurrence rate is still high at 5.9% to 24.5%, even after thoracoscopic stapled bullectomy (Table 5) (18,(22)(23)(24)(25)(26)(27). Therefore, Lee at al.…”
Section: Discussionmentioning
confidence: 99%
“…According to the American College of Chest Physicians (21) and BTS guidelines (4), the preferred approach for prevention of recurrent pneumothorax is still surgical because of lower recurrence rates compared with instillation of sclerosing agents through a chest tube. However, the recurrence rate is still high at 5.9% to 24.5%, even after thoracoscopic stapled bullectomy (Table 5) (18,(22)(23)(24)(25)(26)(27). Therefore, Lee at al.…”
Section: Discussionmentioning
confidence: 99%
“…To compensate for these disadvantages, a coverage procedure after the thoracoscopic bullectomy was introduced. Sakamoto et al reported performance of staple line coverage with an absorbable mesh in 114 patients over a 3-year period with a recurrence rate of only 2.6% in the coverage group and 9.5% in the simple bullectomy group [2]. Kurihara et al combined the absorbable cellulose mesh with fibrin glue to a staple line and reduced the recurrence rate [15].…”
Section: Discussionmentioning
confidence: 99%
“…Kurihara et al combined the absorbable cellulose mesh with fibrin glue to a staple line and reduced the recurrence rate [15]. One of the reasons for postoperative recurrence is reportedly the formation of new blebs near the staple line and this is confirmed by the observation of patients who undergo reoperation [2]. In addition, postoperative air leaks occur mainly at the staple line, as a result of stapling problems, incomplete resection of blebs, emphysematous changes in the resected area, or the crossing of the staple line [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Locating the air-leak site using a thoracoscope is more accurate and effective than is pleurodesis through thoracostomy tube, if the patient is able to tolerate the local and epidural anesthesia. As the polyglycolic acid sheet is absorbable, resistant to infection and easy to manipulate, it has been widely used as a buttress along the staple lines in patients who underwent pulmonary resection and has offered good results with regard to control of air leaks; 8 covering an air-leak site with a piece of polyglycolic acid sheet using a fibrin glue is a simple strategy for persistent air leaks.…”
mentioning
confidence: 99%